Yeh’s Satisfaction Index Modelling of Tenants in Rental Appartments (A Case Study of Latifabad Hyderabad) - Rabia Gill; Saima Kalwar, Dr; Irfan Ahmed Memon, Dr (Sukkur IBA Journal of Computing and Mathematical Sciences, 2021)
The population of urban areas has been rapidly growing for the last few decades, in this way the housing demand increasing including rental apartments in Pakistan, although the satisfaction of tenant toward particular apartment is a big challenge. A recent study on the United States showed that rental household spending constitutes about 25% of total household income, and housing wealth makes up 55% of household net worth which includes; services and facilities like; electricity bill, water supply bill, gas, sanitation, and other maintenance. There are also many problems like; income and affordability, lack of building bylaws. This study finds the satisfaction level of the tenant. A questionnaire survey is used to collect the data regarding particular research and the analysis is done in two parts: (1) analysis of frequency ranking of all amenities, services, and facility types, (2) Yeh’s satisfaction index model to find the satisfaction level of tenants toward particular amenity, service or facility. Findings show issues like; water supply, ventilation, sunlight, age of apartment, electricity, improper cleaning insufficient parking, minimum play area, isolation, over rent, price of services, maintenance, and management, suffocation, congestion, etc. This result implies that rents are more likely to base on provided amenities rather than unit size which reconfirms that rent is driven by amenities provided.